Perception Analysis of Vegetable Experts on Setting Priority for Enhancing Efficiency of Agribusiness and Marketing in Vegetable Sector in India - Shubhadeep Roy , Neeraj Singh , Paresh Chaukhande , Raghwendra Singh , R. N. Prasad and B. Singh, (Indian Journal of Extension Education, 2017)
Agribusiness in terms of linkages in marketing channel, market infrastructure, price stabilization and maintainingliaison between demand and supply is a sine qua non for horticultural crops like vegetables, which are perishable in nature.Poor linkages in the supply chain and poor marketing infrastructure are leading to high and fluctuating consumer pricesfor vegetables and only a small proportion of the consumer rupee reaches to the farmers. There is substantial wastage,deterioration in quality and frequent mismatch between demand and supply of vegetables spatially and over the time.Research and development (R&D) in agribusiness is needed to be revitalised. An effort was made to identify the priorityareas where interventions are required. This study was undertaken by conducting a survey of horticultural and marketingexperts in which major problematic areas in agribusiness of vegetable crops were considered. According to 72 per centrespondents inadequacy of infrastructure and cold storage facilities (Rank-1) is among the most problematic areas whereintervention should be a priority. The other problematic areas are lengthy marketing channel and unorganised marketingsystem (Rank-2), inadequate contract farming in vegetables (Rank-3), inadequate small scale production of qualityprocessed vegetable items (Rank-4), and instability in vegetable price leads to food price inflation (Rank-5) etc.Addressing all the problems at one time is difficult. This study throws some light on the policy makers and researchmanagers to identify the way in which future agribusiness R&D should be directed in vegetable sector.